2019
DOI: 10.20525/ijrbs.v8i3.262
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Audit Committee Characteristics on Environmental and Social Disclosures

Abstract: The main reasons for corporate participation in environmental and social disclosure are stability, development, and continuity through participation in protecting the environment and optimizing the use of available resources. As well as the company practices and participation in society of the most important means to create a good image of the company in the community. There is a rise demand for companies to take accountability for their environmental and societal impacts. A core role of the Audit Committee (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…These results indicate that non-financial disclosures, such as CSR, have not received audit committee attention yet. These results are consistent with the results of the previous studies, which revealed that the effectiveness of the audit committee had an insignificant effect on CSR disclosure (Habbash 2015;Biçer and Feneir 2019).…”
Section: Findings and Discussionsupporting
confidence: 93%
“…These results indicate that non-financial disclosures, such as CSR, have not received audit committee attention yet. These results are consistent with the results of the previous studies, which revealed that the effectiveness of the audit committee had an insignificant effect on CSR disclosure (Habbash 2015;Biçer and Feneir 2019).…”
Section: Findings and Discussionsupporting
confidence: 93%
“…Based on the hypothesis test results in Table 5, the financial expertise of the audit committee has a significance value of -0.0001<0.05, which means that the financial expertise of the audit committee has a significant negative effect on CSR disclosure. This is in line with the results of research by Bicer & Feneir (2019) and Li et al (2012) but inconsistent with the results of the study Mohammadi (2020). Based on POJK Number 55 of 2015, the audit committee must have a minimum of 1 person with an accounting and financial background.…”
Section: Resultsmentioning
confidence: 63%
“…But the different research indicated by (Katmon et al, 2019) audit committee size will increase the quality of CSR because the management audit committee can help in providing information on, higher quality the audit committee meeting and have no influence on CSR. While research (Bicer and Feneir, 2019) the results show that characteristic audit committee, as measured by the size and frequency of meeting them will not affect the CSR disclosure.…”
Section: Introductionmentioning
confidence: 82%